Exploring the training needs of nurses in a selected rehabilitation hospital in enhancing the self-concept of patients with spinal cord injury - Bhana-Pema, Varshika (University of Pretoria, 2024)
Dissertation (MSc (Nursing Education))--University of Pretoria, 2023.